Strategi Perluasan Kesempatan Kerja oleh Dinas Perindustrian dan Tenaga Kerja Kota Surabaya - Shafira Friesilia Putri; Kalvin Edo Wahyudi (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The problem of Indonesia as a developing country is its high population which results in employment problems. The problem that Indonesia always faces in the field of employment is that there are a lot of workers but there are not enough job opportunities, which causes unemployment. The city of Surabaya has the largest number of job seekers in East Java Province. This needs special attention from the Surabaya City government so that job seekers can be absorbed by the job market and create as many job opportunities as possible. The expansion of employment opportunities in the city of Surabaya needs to continue to be pursued through the Department of Industry and Manpower which plays an important role in employment matters. This research aims to find out the strategy of the Department of Industry and Manpower in expanding job opportunities in the city of Surabaya. This research uses 3 (three) strategic management focuses, namely: Strategy Formulation, Strategy Implementation and Strategy Evaluation. The research method used in this research is descriptive with a qualitative approach with data collection techniques using observation, interviews and documentation. The results of this research show that the strategy carried out by the Department of Industry and Manpower to expand employment opportunities is through a program to expand employment opportunities with technical guidance training activities. This program was implemented based on suggestions from the people of Surabaya City with various types of training options.